2004
DOI: 10.1093/brain/awh149
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency oscillations and seizure generation in neocortical epilepsy

Abstract: Neocortical seizures are often poorly localized, explosive and widespread at onset, making them poorly amenable to epilepsy surgery in the absence of associated focal brain lesions. We describe, for the first time in an unselected group of patients with neocortical epilepsy, the finding that high-frequency (60-100 Hz) epileptiform oscillations are highly localized in the seizure onset zone, both before and temporally removed from seizure onset. These findings were observed in all six patients with neocortical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
391
2
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 497 publications
(407 citation statements)
references
References 42 publications
10
391
2
4
Order By: Relevance
“…Initially they were described in hippocampus and entorhinal cortex of patients with TLE (Bragin et al, 1999a(Bragin et al, , 2002bStaba et al, 2002Staba et al, , 2004) using microelectrode recordings. Later they were observed using clinical depth and grid electrodes in patients with temporal lobe epilepsy as well in patients with different types of neocortical epilepsy (Bagshaw et al, 2009;Jacobs et al, 2008;Jirsch et al, 2006;Worrell et al, 2004Worrell et al, , 2008. Whether mechanisms of pathological HFOs observed in the hippocampus of epileptic animals and those observed in the neocortex of epileptic patients are the same or different remains unclear.…”
Section: Evidence For Hfos In Experimental and Clinical Epilepsymentioning
confidence: 99%
“…Initially they were described in hippocampus and entorhinal cortex of patients with TLE (Bragin et al, 1999a(Bragin et al, , 2002bStaba et al, 2002Staba et al, , 2004) using microelectrode recordings. Later they were observed using clinical depth and grid electrodes in patients with temporal lobe epilepsy as well in patients with different types of neocortical epilepsy (Bagshaw et al, 2009;Jacobs et al, 2008;Jirsch et al, 2006;Worrell et al, 2004Worrell et al, , 2008. Whether mechanisms of pathological HFOs observed in the hippocampus of epileptic animals and those observed in the neocortex of epileptic patients are the same or different remains unclear.…”
Section: Evidence For Hfos In Experimental and Clinical Epilepsymentioning
confidence: 99%
“…Recent studies have suggested an important role of HFA in epileptogenesis (Bragin et al, 1999(Bragin et al, , 2000(Bragin et al, , 2004 and in seizure initiation (Allen et al, 1992;Fisher et al, 1992;Bikson et al, 2003;Grenier et al, 2003;Bragin et al, 2005). However, studies specifically on the role of HFA in the preictal state are sparse, generally fail to address the cellular and network mechanisms of its buildup, and in some cases consider it an epiphenomenon (Worrell et al, 2004;Khosravani et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Extending interictal ICEEG interpretation using quantitative techniques, however, have disclosed critical background features relevant to surgical decisionmaking that are not apparent to visual inspection. For example, very high frequency (> 100 Hz), low amplitude activity (< 5 μV) has been associated with the epileptogenic zone (Worrell, Parish et al 2004;Alarcon, Binnie et al 1995;Allen, Fish et al 1992), as has neuronal synchrony recorded from hippocampal microelectrodes (Colder, Wilson et al 1996) and spectrogram measurements of EEG amplitude (Asano, Muzik et al 2004). Such techniques may be used to detect signatures of cortical abnormality that are not necessarily associated with the well known paroxysmal features, and that may be linked to seizures.…”
Section: Introductionmentioning
confidence: 99%